Unplugging mucus in cystic fibrosis and chronic obstructive pulmonary disease - Mall, Marcus A. (Annals of the American Thoracic Society, 2016)
Airway mucus obstruction is a key feature of cystic fibrosis (CF) and chronic obstructive pulmonary disease (COPD). The thin layer of mucus that covers healthy airway surfaces has important protective functions in lung defense. However, excess mucus produces airflow obstruction and provides a nidus for bacterial infection and inflammation. Despite its importance in pathogenesis, understanding of the mechanisms underlying airway mucus obstruction, as well as therapeutic options, remain limited. Studies in the rare genetic disease CF identified airway surface dehydration due to cystic fibrosis transmembrane conductance regulator (CFTR) gene dysfunction as an important disease mechanism that may explain mucus stasis and plugging in a spectrum of muco-obstructive lung diseases, including COPD. This concept is supported by the phenotype of the β-epithelial Na+ channel-transgenic mouse that exhibits airway surface dehydration and develops a spontaneous lung disease that shares key features with CF and COPD, such as airway mucus plugging, chronic neutrophilic inflammation, and structural lung damage. Furthermore, preclinical testing demonstrated that hydration strategies, including osmotically active hypertonic saline and preventive inhibition of the amiloride-sensitive epithelial Na+ channel are effective in unplugging airways in this mouse model of chronic obstructive lung disease. On the other hand, genetic deletion of neutrophil elastase, a potent stimulus for mucus hypersecretion, reduced goblet cell metaplasia and mucin expression but had no effect on mucus obstruction in vivo. Collectively, these studies demonstrate that airway surface dehydration is sufficient to produce mucus obstruction even in the absence of mucus hypersecretion and support further clinical testing of hydrating agents as a promising therapeutic strategy to unplug mucus in CF and COPD.
Gesehen am 06.05.2020
Resolving-URL funktioniert nicht